2015
DOI: 10.1038/ijo.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related immune responses and their impact on surgical outcomes

Abstract: The obesity epidemic represents a critical disease burden with broad clinical consequences. At the same time, obesity has been linked to inferior surgical outcomes and considered a contraindication for some elective surgical procedures. A growing body of mechanistic evidence has accumulated linking obesity to changes of metabolism and immune responses. This concept provides an integrated inflammatory network based on the perception of obesity as a state of chronic low-grade inflammation. With a more detailed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 96 publications
1
33
0
2
Order By: Relevance
“…This contrasts the epidemiological evidence linking obesity with poor survival for several other types of cancer (e.g., colon, leukemia). [7][8][9][10] Lung cancer is one of the leading malignancies and causes of death worldwide, 11 and obesity has become a major risk factor for cancer. Given the increasing comorbidity of obesity and lung cancer, new complexity lies ahead for thoracic oncologists to deliberate on the exact impact of obesity on lung cancer treatment and survival.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts the epidemiological evidence linking obesity with poor survival for several other types of cancer (e.g., colon, leukemia). [7][8][9][10] Lung cancer is one of the leading malignancies and causes of death worldwide, 11 and obesity has become a major risk factor for cancer. Given the increasing comorbidity of obesity and lung cancer, new complexity lies ahead for thoracic oncologists to deliberate on the exact impact of obesity on lung cancer treatment and survival.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3)(4) Bariatric surgery affects obesity-induced inflammation through upregulation of adiponectin and IL-10, reduction in pro-inflammatory cytokines, and induction of a reparative T cell phenotype. (18) We showed that SG in rats reduced jejunal IL-17 and IL-23 as well as distal jejunal INFγ, which correlated with weight loss and improved glucose handling. (19) Additionally, in a longitudinal human study of SG-induced circulating immunologic phenotype, we identified a reduction in the neutrophil to lymphocyte ratio, circulating IL-6, and circulating CRP levels across subjects (unpublished).…”
Section: Introductionmentioning
confidence: 83%
“…This likely reflects, at least in part, the relationship between obesity and risk of complications . Even in the absence of specific complications, obesity may slow the process of recovery due to chronic overstimulation of inflammatory pathways . The average financial charges related to care was also significantly higher for patients with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…High body weight exacerbates the risk of many forms of negative physical health outcomes and creates a low‐level but chronic state of elevated inflammation throughout the body, impairing immune functioning . Body mass index (BMI) is often used to define high body weight, with a BMI of 25.0 kg/m 2 or greater indicating overweight status, and a BMI of 30.0 kg/m 2 or greater indicating obesity .…”
Section: Introductionmentioning
confidence: 99%